Hazard of polystyrene micro-and nanospheres to selected aquatic and terrestrial organisms - Qiao, Ruxia; Mortimer, Monika; Richter, Jelizaveta; Rani-Borges, Bárbara [UNESP]; Yu, Zhenyang; Heinlaan, Margit; Lin, Sijie; Ivask, Angela (Elsevier, 2022)
Plastics contamination in the environment is a major concern. Risk assessment of micro- and nanoplastics (MPL and NPL) poses significant challenges due to MPL and NPL heterogeneity regarding compositional polymers, particle sizes and morphologies in the environment. Yet, there exists considerable toxicological literature on commercial polystyrene (PS) micro- and nanospheres. Although such particles do not directly represent the environmental MPL and NPL, their toxicity data should be used to advance the hazard assessment of plastics. Here, toxicity data of PS micro- and nanospheres for microorganisms, aquatic and terrestrial invertebrates, fish, and higher plants was collected and analyzed. The evaluation of 294 papers revealed that aquatic invertebrates were the most studied organisms, nanosized PS was studied more often than microsized PS, acute exposures prevailed over chronic exposures, the toxicity of PS suspension additives was rarely addressed, and ∼40 % of data indicated no organismal effects of PS. Toxicity mechanisms were mainly studied in fish and nematode Caenorhabditis elegans, providing guidance for relevant studies in higher organisms. Future studies should focus on environmentally relevant plastics concentrations, wide range of organisms, co-exposures with other pollutants, and method development for plastics identification and quantification to fill the gap of bioaccumulation assessment of plastics.
Keywords: Fish; Invertebrates; Microorganisms; Microplastics; Nanoplastics; Plants